The cultural mosaic of ethnic groups in Vietnam: First English edition, with amendments and additions - Nguyen Van Huy (Education publishing house, 2001)
Trình bày những nét văn hóa, địa lý, dân số, lịch sử, hoạt động sản xuất... của 54 dân tộc thiểu số ở Việt Nam.